ANALYSIS SCHEDULING PROJECT USING CPM METHOD (Case study : Project of the Surabaya Caspian Tower Apartment) - Harjian Maprilana; Koespiadi Koespiadi (IJEEIT : International Journal of Electrical Engineering and Information Technology, 2019)
The success and failure of project implementation is often caused by poor planning and ineffective controls, so that project activities experience various obstacles such as the late completion of the project, the decline in the quality of work and the swelling of implementation costs. Project management is carried out to manage the project from the beginning of the project until the completion of the project properly. The case study in this study is PT. PP (Persero) Tbk. as the executing element of the construction work, it is in charge of organizing the construction of the Surabaya Caspian Tower Apartment in East Java. The CPM (Critical Path Method) method is used to find out how long a project has been completed and look for possible acceleration of project time. From the research using the CPM method, it can be seen that the normal duration of project completion is 453 days which can be optimized to 350 days. This can be done by giving special attention to activities included in the critical path and accelerating some activities by increasing the number of workers